EFEKTIVITAS PENGGUNAAN E-LEARNING DALAM PROSES PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - wahyu dewanti; eni rombe; fianus tandiongan (STT Kristus Alfa Omega, 2022)
Effectiveness is understood as a level of success produced by a person or organization in a certain way in accordance with the goals to be achieved. State Junior High School 1 Tayu uses e-learning in the learning process of Christian Religious Education. E-learning is a medium that can be used in the distance learning process. There is an allegation that the effectiveness of the use of e-learning is not optimal in the learning process of Christian Religious Education at the State Junior High School 1 Tayu. This is evidenced by the discovery of the obstacles that occur. This study aims to find out how effective the use of e-learning is in the learning process of Christian Religious Education at Tayu 1 State Junior High School. This is very important because E-Learning must be developed at SMP Negeri 1 Tayu. If this is not followed up, problems will arise in the use of E-Learning in the Christian Religious Education learning process. The method used in this research is using descriptive qualitative research methods.The results of the research conducted are the effectiveness of the use of e-learning in the learning process of Christian Religious Education at SMP Negeri 1 Tayu has been used quite well, meaning that the use of e-learning is quite effective. According to the findings, researchers still find obstacles experienced by educators and students in the use of e-learning.